The Effect of the CIRC (Cooperative Integrated Reading and Composition) Learning Model on the Basic Literacy Skills of Fourth Grade Students at SDN Inpres - Nurfadillah, Nurfadillah; Ningsih, Suriya; Khusaini, Fakhri (Journal of Educational Sciences, 2025)
This study aims to analyze the effect of the Cooperative Integrated Reading and Composition (CIRC) learning model on the basic literacy skills of fourth-grade students at SDN Inpres Lesu. The research employed a quantitative approach with a one-group pretest-posttest design involving 10 students. Data were collected through literacy tests, observations, and documentation. The pretest results showed an average score of 53.9, which increased to 77.9 in the posttest. The Shapiro-Wilk normality test indicated that the data were normally distributed (p > 0.05), allowing for further analysis using a paired sample t-test. The test results yielded a significance value of 0.000 (p < 0.05), indicating a significant difference before and after the treatment. The implementation of CIRC proved effective in enhancing students’ reading, comprehension, and written expression skills through collaborative group work. These findings suggest that interactive and cooperative learning strategies such as CIRC are highly applicable in Indonesian language instruction at the elementary school level to strengthen students’ literacy.